Self-Imposed Temporal Redundancy: An Efficient Technique to Enhance the Reliability of Pipelined Functional Units - Mizan, Elias; Amimeur, Tileli; Jacome, Margarida F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2007: Anais do XIX International Symposium on Computer Architecture and High Performance Computing, 2007)
Temporal redundancy (TR) improves the reliability of computational functional units (FUs). However, it can guarantee detection of transient errors only, and may have a substantial power and area overhead. In this paper we present self-imposed temporal redundancy (SITR), a form of TR that can be applied to pipelined FUs and does not suffer from the aforementioned problems. A SITR-enhanced FU forces redundant computations to fire in consecutive cycles and requires a single additional cycle for the second computation and the comparison of the two results. We evaluate the power and area overhead of SITR and conclude that is always smaller than that of standard TR and that it does not depend on the FU complexity. We also use SITR to improve the reliability of the execution datapath of a simple out-of-order engine, typical of that used in high reliability embedded systems and future many-core architectures. Our simulations show that SITR outperforms TR, especially in FP applications. When the number of integer ALUs is larger than the machine width, the performance penalty of SITR is consistently less than 10%.